Olivetti’s New Canaan Electronic Laboratory: when design meets computing - Rocha, João (2018)
The development of computer technology and its application by architectural research centres is a recent area of study. Initial research focused on the early work in design and computation that took place in university centres, their key figures and the theoretical and practical advances. Within this context, this paper aims to unveil the historical role played by the Olivetti Company and its Electronics Research Laboratory in New Canaan, US in shaping the first fully transistorized computer in the world and also in inaugurating multidisciplinary design research within the field. Founded in 1952, the laboratory worked closely with its main headquarters in Italy, introducing many technological innovations into the design process for new Olivetti electronic products. The paper draws on research conducted at the Olivetti archive, presenting a broader view of Olivetti's contribution to the field of computing and its innovative aesthetics. The work of Dino Olivetti, Ettore Sottsass and Mario Tchou was fundamental to this endeavour, anticipating what would become the concept of personal computing.